Adaptation and validation of the Portuguese version of the regulation of eating behavior scale (REBSp). (1st January 2021) - Teixeira, D.S.; Pelletier, L.; Encantado, J.; Marques, M.M.; Rodrigues, B.; Carraça, E.V.
Abstract: The aim of present study was two-fold: i) to translate and adapt the Regulation of Eating Behavior Scale to Portuguese (REBSp), and ii) to analyze its psychometrics properties (factorial validity with gender invariance analyses, reliability and construct validity). The study sample was composed by 471 Portuguese participants (68.4% females) with a mean age of 30.5 years (SD = 11.2). Structural equation modeling was used to verify the psychometric properties of the scale using SPSS v. 23.0 and AMOS 24.0 software. The analysis showed that the Portuguese 24-item scale presented a good fit, achieving good reliability and convergent validity. Some issues arose with discriminant validity within autonomous and controlled regulations, discussed in light of the simplex pattern expected by self-determination theory literature. Additionally, the scale presented concurrent validity and evidence of gender measurement invariance. Latent mean analysis between genders showed that women presented higher means for intrinsic motivation and integrated regulation when compared to men. In conclusion, analyses suggest that the 24-item Portuguese version of REBS can be used safely to assess the eating regulation in both genders.